Avaliação imunoistoquimica da cérvix de cadelas saudáveis e com o diagnóstico de piometra - Volpato, Rodrigo [UNESP] (2015)
The aim of this study was to evaluate the mechanisms involved in cervical opening in bitches with pyometra and healthy bitches. To this end, immunohistochemical evaluations were conducted in different regions of the cervix, epithelium luminal, glandular and musculene for e-NOS, i-NOS, FAS, FAS-L, PGF2α-R and COX-2 receptors. For this purpose, were used 11 bitches with open pyometra, 11 bitches with close pyometra, 6 healthy bitches on follicular phase and 6 on luteal phase of the estrous cycle. All females were subjected to ovariohysterectomy (OSH) and serum progesterone were performed to confirm the phase of the estrous cycle. The measurements were performed using solid phase commercial kits. For immunostaining evaluation two methods were used. In the first, five fields were evaluated in each of these tissues, where each field received a score from 0 to 4 (0 = 0 to 5% of positive field, 1 = 5 to 25% of positive field, 2 = 25 to 50%, 3 = 50 to 75% of positive field and 4 = 75 to 100% of positive field) being considered positive those stained in brown and blue the negative ones. In the second method the markings intensity was assessed subjectively in weak, moderate and strong, respectively receiving scores 1, 2 and 3 for statistical analysis. Readings were taken at five random fields, that were all homogeneous (more than 80% of the staining with the same intensity). The evaluations were performed using a light microscope at a magnification of 400x. Non-parametric statistical test of Mann-Whitney was performed to compare the presence, concentration of each receiver and the region between the closed and open pyometra groups. Among pyometra, follicular phase and luteal phase groups, Kruskall-Wallis test was used, once the comparison made was between three independent groups. The i-NOS and FAS receptors behave in the same way in bitches with open and closed pyometra, not being involved in cervical opening mechanism in this disease. The ...